Evidence-based strategies for extreme poverty reduction: Identifying priority areas in Jambi Province, Indonesia - Zulgani, Zulgani; Zevaya, Faradina; Asfahani, Fadwa Rhogib (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2025)
Extreme poverty is a global priority within the framework of the Sustainable Development Goals (SDGs), with “No Poverty” designated as Goal 1 by the United Nations. Indonesia has targeted the eradication of extreme poverty to 0–1% by 2024, requiring each region to accelerate its efforts, including Jambi Province, which recorded an average extreme poverty rate of 1.36% in 2021. This study aims to identify priority areas of extreme poverty in Jambi Province and to formulate evidence-based strategies through the integration of spatial mapping using the Extreme Poverty Coefficient (K₀) with the Analytical Hierarchy Process (AHP). The analysis employed district/municipality-level data for the period 2021–2022, with K₀ constructed from official BPS indicators and AHP conducted through expert assessments across institutions. The findings reveal shifts in priority areas: in 2021, the highest-priority regions were Tanjung Jabung Barat, Tanjung Jabung Timur, and Jambi City, while in 2022, Sarolangun and Batang Hari emerged as new high-priority areas. The AHP results indicate that reducing household expenditure burdens is the main strategic criterion (0.748), followed by reducing poverty pockets (0.134) and increasing community income (0.119). The most prominent policy alternatives include food subsidies, energy subsidies, and the empowerment of local economies and MSMEs. Methodologically, this study contributes by integrating K₀-based spatial mapping with AHP to produce policy strategies that are convergent, measurable, and place-based. These findings are expected to strengthen Indonesia’s efforts to accelerate the eradication of extreme poverty.